Dominant Cultural and Personal Stigma Beliefs and the Utilization of Mental Health Services: A Cross-National Comparison - Bracke, Piet; Delaruelle, Katrijn; Verhaeghe, Mieke (Frontiers in Sociology, 2019)
Purpose. Several studies have already revealed a negative relationship between stigma and mental health service use. Nevertheless, only few of them explicitly separate the cultural from the personal dimension of stigma. This contribution focuses on the distinction between cultural stigma beliefs and personal stigma beliefs, using a cross-national comparative research design. Methods. The effects of both types of stigma on different types of mental health service use in 28 European countries (data from the Eurobarometer 248 on mental well-being) are estimated, net of the effect of need. Results reveal that in countries with more cultural stigma beliefs people are less eager to seek professional help for mental health problems in general, and from mental health specialists, irrespective of their personal beliefs. Finally, in those countries, persons with higher needs also refrain from contacting general practitioners for their mental health problems. Conclusion. Stigma beliefs are a shared cultural phenomenon that limits professional care seeking, in addition to personal stigma beliefs. Research that on focus on the latter underestimates the pervasive effects of stigma beliefs. The present study signals the importance of expectations of devaluation and discrimination as barriers to professional care seeking in highly stigmatizing countries.